A van der Waals Integrated Damage‐Free Memristor Based on Layered 2D Hexagonal Boron Nitride. Issue 12 (27th January 2022) - Mao, Jing‐Yu; Wu, Shuang; Ding, Guanglong; Wang, Zhan‐Peng; Qian, Fang‐Sheng; Yang, Jia‐Qin; Zhou, Ye; Han, Su‐Ting
Abstract: 2D materials with intriguing properties have been widely used in optoelectronics. However, electronic devices suffered from structural damage due to the ultrathin materials and uncontrolled defects at interfaces upon metallization, which hindered the development of reliable devices. Here, a damage‐free Au/h‐BN/Au memristor is reported using a clean, water‐assisted metal transfer approach by physically assembling Au electrodes onto the layered h‐BN which minimized the structural damage and undesired interfacial defects. The memristors demonstrate significantly improved performance with the coexistence of nonpolar and threshold switching as well as tunable current levels by controlling the compliance current, compared with devices with evaporated contacts. The devices integrated into an array show suppressed sneak path current and can work as both logic gates and latches to implement logic operations allowing in‐memory computing. Cross‐sectional scanning transmission electron microscopy analysis validates the feasibility of this nondestructive metal integration approach, the crucial role of high‐quality atomically sharp interface in resistive switching, and a direct observation of percolation path. The underlying mechanism of boron vacancies‐assisted transport is further supported experimentally by conductive atomic force microscopy free from process‐induced damage, and theoretically by ab initio simulations. Abstract : A damage‐free Au/h‐BN/Au memristor fabricated using a metal transfer approach is demonstrated. Au electrodes are physically assembled onto layered h‐BN with minimized damage and interfacial defects. The Au/h‐BN/Au memristors demonstrate superior performance with the coexistence of nonpolar and threshold switching and can further implement logic functions. Cross‐sectional STEM validates the feasibility of this nondestructive approach, the crucial role of sharp interface, and a direct observation of percolation path.